2019
DOI: 10.1155/2019/5735702
|View full text |Cite
|
Sign up to set email alerts
|

Review of Urban Transportation Network Design Problems Based on CiteSpace

Abstract: This paper provides a comprehensive review of urban transportation network design problems according to CiteSpace, including main problem classifications, mathematical models, and solution methods obtained from CiteSpace clusters. The review attempts to present the systematic picture of urban transportation network design and show the future directions of it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 80 publications
0
20
0
2
Order By: Relevance
“…In the literature, studies concerning TNDP addresses strategic issues (route generation, network design, and frequency setting) and tactical issues (timetabling of transit lines and vehicle and crew scheduling); seminal works in this field are [3][4][5][6][7][8][9][10], and a recent review of the mathematical models and solution methods for the TNDP can be found in [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, studies concerning TNDP addresses strategic issues (route generation, network design, and frequency setting) and tactical issues (timetabling of transit lines and vehicle and crew scheduling); seminal works in this field are [3][4][5][6][7][8][9][10], and a recent review of the mathematical models and solution methods for the TNDP can be found in [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Among available strategies, providing dedicated lanes to autonomous vehicles using existing infrastructure is a flexible and low-cost one. It is a tactical decision which can benefit the network through existing resources [10]. However, conversion of a general purpose lane to a dedicated lane may lead to public dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, Traffic lights optimization using adaptive and intelligent algorithms in conjunction with smart sensing is a must under these circumstances. This comes under design optimization, where smart algorithms such as genetic and fuzzy logic algorithms are employed to improve an existing transportation network as a function of increasing level of traffic flow levels, resulting in traffic congestion, delays, higher fuel consumption, air pollution and increase probability of traffic incidents [1][2].…”
Section: Introductionmentioning
confidence: 99%